SAT-670 The Perfect Storm for Diabetic Ketoacidosis - Abushamat, Layla A (J Endocr Soc, 2020)
Background Diabetic Ketoacidosis (DKA) is a life-threatening endocrine emergency characterized by metabolic acidosis occurring in the setting of hyperglycemia due to relative insulin deficiency leading to lipolysis and production of serum ketones. Clinical circumstances can potentiate this process, such as acute infection or insulin discontinuation. Additionally, patients on SGLT2-inhibitors are at risk for euglycemic DKA. In people with type 2 diabetes, DKA is uncommon; however, a combination of precipitating factors in these patients can lead to a greater risk of DKA, particularly in the setting of SGLT2-inhibitor use. Clinical Case A 63 year old male with past medical history significant for uncontrolled type 2 diabetes (10 year duration, HgA1c=11.2%, on insulins detemir and aspart, metformin, and empagliflozin), coronary artery disease, and treatment refractory antibody-negative polymyositis (baseline CPK levels ~1000-2000, on a burst of prednisone for flare) presented with fever (101.2F), fatigue, myalgias, and nausea with poor oral intake and insulin cessation after recent IV zoledronic acid infusion for prevention of steroid-induced osteoporosis. He was found to be acidemic with bicarbonate=16, AG=18, Cr=1.6 (baseline 1.1), lactic acid=2.9, glucose=245, glucosuria/ketonuria, serum osmolality=295, and CPK=3613. No infectious etiology was found. Differential diagnosis of precipitating factors of DKA includes: steroid-induced hyperglycemia with lipolysis and insulin resistance; starvation ketosis from poor oral intake due to bisphosphonate-induced flu-like illness; metformin-associated lactic acidosis in setting of acute kidney injury; ketone production secondary to insulin cessation in setting of febrile illness; and SGLT2-inhibitor use with dehydration secondary to decompensated hyperglycemia. He was treated for DKA with insulin and volume resuscitation. He was discharged with discontinuation of empagliflozin. Conclusion In people with type 2 diabetes and multiple medical problems, a collusion of clinical factors leading to acidemia can occur simultaneously and lead to a drastically increased risk of DKA, especially in the setting of SGLT2-inhibitor use. Clinicians should have heightened awareness of minor predisposing factors that in combination can increase risk of DKA in a patient with type 2 diabetes.